Questioning the Implementation of Value Added Tax on Educational Services in Indonesia - Andini, Puspita; Tambunan, Maria R.U.D. (Law Review, 2025)
Law Number 7 of 2021 on Tax Regulation Harmonization has ushered in notable alterations to the Value Added Tax (VAT) stipulations within Indonesia. Notably, this law now classifies educational services as taxable entities. This study examines the background of the VAT policy on education services and evaluates it. Adopting a post-positivist approach, the research utilizes literature studies and in-depth interviews for data collection. The research shows that such a shift in policy raises concerns about legal clarity and the methods for imposing VAT. Amid public disapproval, the authorities opted to subject educational services to VAT but with certain exemptions. Despite these tax breaks, education service providers still must issue tax invoices, potentially elevating their compliance costs. However, the tax authorities have yet to provide detailed guidance on how this law affects educational service providers in terms of subjects, objects, and VAT bases. Based on the conducted research, the advised steps forward include specifying which educational services are impacted, ensuring clear communication about the legal aspects of educational services, and facilitating administrative procedures for taxpayers to meet their responsibility.